2013
DOI: 10.1155/2013/473764
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Visceral Fat Accumulation Awareness on a Web-Based Weight-Loss Program: Japanese Study of Visceral Adiposity and Lifestyle Information—Utilization and Evaluation (J-VALUE)

Abstract: A reduction of visceral fat is important for improvement of metabolic risk. This study was designed to compare the effects of a web-based program alone or together with measurement and self-awareness of accumulated visceral fat in Japanese workers. A new noninvasive device to measure visceral fat accumulation was introduced, and efficacy on weight-loss and improvement of healthy behaviors were examined. This study was conducted according to Helsinki declaration and approved by the ethical committee of Japan Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The zoometric parameters are mostly used to evaluate the degree of obesity are AC and BMI, which have been associated with the risk of cardiovascular diseases [60], and mortality in patients with type 2 diabetes [61], although these are rarely assessed in assays with rats. The AC decreased in ABD10(E) and ABD20(E) rats after 8 weeks of consumption of the these diets including A. dubius, which is a relevant indicator of the reduction in visceral fat, which at the same time reduces the risk of metabolic syndrome [62], possibly influenced by the high fibre content in A. dubius [24,42,63]. It is well known that fibre increases satiety and reduces intestinal transit time and glycaemic response.…”
Section: Discussionmentioning
confidence: 99%
“…The zoometric parameters are mostly used to evaluate the degree of obesity are AC and BMI, which have been associated with the risk of cardiovascular diseases [60], and mortality in patients with type 2 diabetes [61], although these are rarely assessed in assays with rats. The AC decreased in ABD10(E) and ABD20(E) rats after 8 weeks of consumption of the these diets including A. dubius, which is a relevant indicator of the reduction in visceral fat, which at the same time reduces the risk of metabolic syndrome [62], possibly influenced by the high fibre content in A. dubius [24,42,63]. It is well known that fibre increases satiety and reduces intestinal transit time and glycaemic response.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 30 included studies, the outcome variable was BMI in 19 (63%) studies [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82], waist circumference in 25 (83%) studies [64,66,[68][69][70][71][72][73][74][75][76][78][79][80][81][82][83][84][85][86][87][88][89][90][91], and body fat percentage in 11 (37%) studies [64,70,72,73,76,78,80,…”
Section: Overviewmentioning
confidence: 99%
“…The mean age of the participants was 40.2 (SD 17.1) years. In a study by Sakane et al [79], the average age was not reported, but the age range of the participants was used. Therefore, the average age was imputed from the average age of Japanese people aged 20-65 years [94], weighted with the proportions of men and women in the study.…”
Section: Description Of the Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these devices simply output an estimated square measure of the visceral fat area (VFA). It would be desireble to obtain a more visually persuasive output, which would strongly motivate the patient to modify his/her lifestyle and reduce visceral fat accumulation by exercising and changing his/her dietary habits …”
Section: Introductionmentioning
confidence: 99%